Math, asked by viswas1234, 10 months ago

pls answer really quick useless answers will be reported pls really urgent​

Attachments:

Answers

Answered by Nigamaasdfghjkl
1

Answer:

Step-by-step explanation:

the answer of c-question ,we have to use the formula a^m into a^n=a^m+n.so,                                                                                             (4/7)^3+(-6)=(4/7)^-3.they have asked to find m.BASES ARE EQUAL,SO POWERS ARE ALSO EQUAL.so,-3=2m-1.so,-3+1=2m.so,-2=2m.so,m=-1

Similar questions